Applying intervention mapping to develop a program for promoting short physical activity breaks during class time in upper secondary schools: the MOVE12 protocol study - Barene, Svein; Johansen, Patrick Foss; Tjomsland, Hege Eikeland; Ølberg, Rolf Inge; Thurston, Miranda (Frontiers in Sports and Active Living, 2025)
IntroductionPhysical inactivity is a global health challenge, exacerbated by increased screen time and sedentary behaviors. Enhancing physical activity levels at schools offers a promising approach to promote lifelong healthy habits.MethodsThis protocol paper outlines the MOVE12 pilot study, a 12-week intervention study designed to increase physical activity among Norwegian upper secondary school students through 6–7-min daily MOVE-breaks integrated into lessons. Developed using the six-phase Intervention Mapping (IM) protocol, grounded in the social-ecological model and self-determination theory, the intervention focuses on fostering motivation and creating a supportive environment. Key steps include needs assessment, performance objectives, theoretical methods, and program structuring for sustainability.ResultsLinear mixed models, t-tests, and regression analyses will evaluate quantitative outcomes, while qualitative focus groups will explore engagement and behavior change.DiscussionMOVE12 provides insights into scalable school-based interventions addressing physical inactivity, highlighting the potential of the IM framework to establish sustainable health promotion strategies.